Optimising the K Dark Filter for the Kunlun Infrared Sky Survey. (10th March 2016) - Li, Yushan; Zheng, Jessica; Tuthill, Peter; Freeman, Matthew; Ashley, Michael; Burton, Michael; Lawrence, Jon; Mould, Jeremy; Wang, Lifan
Abstract: The Kunlun Infrared Sky Survey will be the first comprehensive exploration of the time varying Universe in the infrared. A key feature in optimising the scientific yield of this ambitious research programme is the choice of the survey passband. In particular, the survey aims to maximally exploit the unique thermal and atmospheric conditions pertaining to the high Antarctic site. By simulating the expected signal-to-noise for varying filter properties within the so-called ' K DARK' 2.4 μm window, filter performance can be tuned and best-case designs are given covering a range of conditions.